Government Policy in Implementing the Issuance of Sailing Permits In Cirebon Port - Didi Nursidi (Penerbit Hellow Pustaka, 2025)
The issuance of Sailing Permit (SIB) in its implementation still has the application of application requirements that are applied outside the applicable provisions, for example additional costs, for that it is necessary to make consistent enforcement efforts, so that an efficient service system is created. For this purpose, the Port Administrator needs to improve the one-stop integrated licensing pattern so that efforts to make Cirebon Port an International Sea Port have a high level of competitiveness.